Multifunctional efficiency metric for structural supercapacitors. Issue 4 (22nd December 2020) - Zhou, Tianyang; Dickinson, Emma; Boyd, James G; Lutkenhaus, Jodie L; Lagoudas, Dimitris C
Abstract: A new energy-based multifunctional efficiency (MFE) metric is developed using micromechanics solutions for structural supercapacitors consisting of composite electrodes that can store electrical energy and sustain mechanical loads. MFE metrics quantify the volume and/or mass savings when structural and functional materials are replaced by multifunctional materials and evaluate the trade-off between different functionalities. Commonly used multifunctionality metrics for structural supercapacitors are based on the rule of mixtures for both mechanical and electrical performance. These metrics provide an adequate approximation for some electrode geometries and loading conditions, such as longitudinal direction for aligned fibers in multifunctional composite electrodes and in-plane directions for laminate composite electrodes. However, if supercapacitors with complex microstructure or multiple electrode materials encompass more complex geometries or orientations of the structural and functional phases, a more comprehensive method is required to accurately capture the MFE. The MFE proposed herein can account for complex geometries and different mechanical loading conditions by using micromechanics methods. The shapes considered here include layered composite supercapacitors, fibrous films and any shape that can be derived from an ellipsoid. When calculated utilizing the proposed metric, the MFE varies by orders of magnitude due to the difference in shapes and applied mechanical fields to the supercapacitors, while existing metrics provide a constant upper bound. The influence of Young's modulus difference between multifunctional electrodes and solid electrolytes is also discussed.